TORPP - Turtles, One Health Research & Plastic Pollution: A multidisciplinary consortium to evaluate the environmental and health impact of Micro/NanoPlastics (MNPs) pollution - A. Legrand; G. Blanvillain; T. Deschamps; G. Chapelet; F. Aubret; L. Garrido; S. Lecomte; A. Martinez-Silvestre; J.C. Auguet; A. Sauvaget (One Health)
Although the World Health Organization characterizes a One Health concern as one in which there is the capability to incorporate numerous disciplines to tackle health challenges threatening humans, animals and ecosystems, scientific efforts frequently remain compartmentalized. Here we report an original consortium, TORPP, spanning 16 disciplines, focused on Micro/NanoPlastics (MNPs) pollution as a One Health concern. Whereas the MNP topic has been largely studied in marine ecology, research effort remains scarce in human medicine. Equally, while marine ecology is highly skilled in MNP sampling and characterization, human medicine has developed pathophysiological concepts and tools that can be used more broadly to evaluate the health impact of MNPs. TORPP consortium propose that these strengths and knowledges must be transferred across fields of study to advance our understanding of MNP toxicity to organisms, by uniting integrative approaches (ecological, experimental and clinical) under a common conceptual and analytical framework.